Trade Liberalization and Firm Productivity : The Case of India - Topalova, Petia (IMF Working Papers; Working Paper ;, 2004)
Using a panel of firm-level data, this paper examines the effects of India's trade reforms in the early 1990s on firm productivity in the manufacturing sector, focusing on the interaction between this policy shock and firm and environment characteristics. The rapid and comprehensive tariff reductions-part of an IMF-supported adjustment program with India in 1991-allow us to establish a causal link between variations in inter-industry and intertemporal tariffs and consistently estimated firm productivity. Specifically, reductions in trade protectionism lead to higher levels and growth of firm productivity, with this effect strongest for private companies. Interestingly, state-level characteristics, such as labor regulations, investment climate, and financial development, do not appear to influence the effect of trade liberalization on firm productivity.